1998
DOI: 10.1002/(sici)1098-2280(1998)32:1<39::aid-em5>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic damage and induction of pro-oxidant state in human lymphocytes exposed in vitro to gliphosate, vinclozolin, atrazine, and DPX-E9636

Abstract: We analyzed chromosome aberrations (CAs), sister chromatid exchanges (SCEs), mitotic index (MI), and glucose 6‐phosphate dehydrogenase (G6PD) enzyme activity in human peripheral lymphocytes from three healthy donors exposed in vitro to different concentrations of gliphosate, vinclozolin, atrazine, and DPX‐E9636. The pesticides gliphosate, vinclozolin, and atrazine have been studied in a broad range of genetic tests with predominantly conflicting or negative results, whereas little is known about the genotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
44
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 32 publications
7
44
1
2
Order By: Relevance
“…Because this specific biologic pathway operates only in plants and microorganisms, the mechanism is not considered to be a risk for humans. Nevertheless, genotoxic, hormonal, and enzymatic effects of glyphosate in mammals have been reported [20, 2225]. In rats, glyphosate was found to decrease the activity of some detoxifying enzymes, cytochrome P-450, and monooxygenase activities and the intestinal activity of aryl hydrocarbon hydroxylase when injected into the abdomen [26].…”
Section: Introductionmentioning
confidence: 99%
“…Because this specific biologic pathway operates only in plants and microorganisms, the mechanism is not considered to be a risk for humans. Nevertheless, genotoxic, hormonal, and enzymatic effects of glyphosate in mammals have been reported [20, 2225]. In rats, glyphosate was found to decrease the activity of some detoxifying enzymes, cytochrome P-450, and monooxygenase activities and the intestinal activity of aryl hydrocarbon hydroxylase when injected into the abdomen [26].…”
Section: Introductionmentioning
confidence: 99%
“…Glyphosate did not show any genotoxic activity in a battery of assays (Garry et al 1999; Grisolia 2002; Li and Long 1988; Wildeman and Nazar 1982). However, other studies observed that glyphosate treatment of human lymphocytes in vitro resulted in increased sister chromatid exchanges (Bolognesi et al 1997), chromosomal aberrations (Lioi et al 1998b), and indicators of oxidative stress (Lioi et al 1998b). Some studies found slightly greater toxicity of the Roundup formulation compared with glyphosate, in terms of both acute toxicity (Folmar et al 1979; Martinez et al 1990; Mitchell et al 1987) and genotoxicity (Bolognesi et al 1997; Vigfusson and Vyse 1980).…”
mentioning
confidence: 99%
“…Because this specific biologic pathway operates only in plants and microorganisms, the mechanism is not considered to be a risk for humans. Nevertheless, genotoxic, hormonal, and enzymatic effects in mammals have been reported (Bolognesi et al 1997; Daruich et al 2001; El Demerdash et al 2001; Hietanen et al 1983; Lioi et al 1998a, 1998b; Olorunsogo et al 1979; Peluso et al 1998; Walsh et al 2000; Yousef et al 1995). …”
mentioning
confidence: 99%
“…As the identification of copy number variation within the zebrafish genome has been completed (Brown et al, 2012), this initial assessment utilized zebrafish fibroblast cells for the study of CNA formation following atrazine exposure to eliminate detection of copy number variants that would be present among different individual fish. The genotoxicity of atrazine has been under investigation and has produced conflicting results which have ranged from evidence of no genotoxicity (Kligerman et al, 2000a; Surrallés et al, 1995; Zeljezic et al, 2006), to the generation of chromosomal aberrations (CA), sister chromatid exchanges (SEC), and increases in coefficient of variation (CV) at various dose levels and exposure periods (Biradar and Rayburn, 1995; Lioi et al, 1998; Rayburn et al, 2001; Taets et al, 1998). …”
Section: Discussionmentioning
confidence: 99%
“…The majority of in vitro studies have been conducted in Chinese hamster ovary (CHO) and human lymphocyte cells. Positive studies indicate that atrazine elicits genotoxicity through chromosomal aberrations (CA), sister chromatid exchanges (SCEs), and increases in the coefficient of variation (CV) at a variety of concentrations and exposure periods (Biradar and Rayburn, 1995; Lioi et al, 1998; Rayburn et al, 2001; Taets et al, 1998). While contrasting studies do not demonstrate any significant genotoxicity (Dunkelberg et al, 1994; Kligerman et al, 2000a, 2000b; Roloff et al, 1992; Surrallés et al, 1995; Zeljezic et al, 2006).…”
Section: Introductionmentioning
confidence: 99%